2015
DOI: 10.1017/s0033291715001841
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic experiences and risk of self-injurious behaviour in the general population: a systematic review and meta-analysis

Abstract: PE are associated with self-injurious behaviour, suggesting they have potential as passive markers of suicidality. However, the association is confounded and several methodological issues remain, particularly how to separate PE from the full range of connected psychopathology in determining any specific association with self-injurious behaviour. Given evidence that PE represent an indicator of severity of non-psychotic psychopathology, the association between PE and self-injurious behaviour probably reflects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 65 publications
(112 reference statements)
11
85
0
3
Order By: Relevance
“…Recently, PE have been identified as a risk factor for suicidal ideation and behaviour in general population individuals (Honings et al, 2015). A similar association has been reported for individuals at risk for psychosis (Taylor et al, 2015).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Recently, PE have been identified as a risk factor for suicidal ideation and behaviour in general population individuals (Honings et al, 2015). A similar association has been reported for individuals at risk for psychosis (Taylor et al, 2015).…”
Section: Introductionsupporting
confidence: 61%
“…A recent meta-analysis concluded that general population individuals with PE are at increased risk of suicidal ideation and behaviour, but that this association is confounded by the presence of co-occurring non-psychotic psychopathology (Honings et al, 2015). The reported association between PE and suicidal ideation and behaviour was hypothesized to reflect the increased risk of these outcomes in distressed participants with comorbid mental disorders or high levels of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations